2020
DOI: 10.1242/jeb.221895
|View full text |Cite
|
Sign up to set email alerts
|

Both maternal and embryonic exposure to mild hypoxia influence embryonic development of the intertidal gastropod Littorina littorea (Linnaeus, 1758)

Abstract: There is growing evidence that maternal exposure to environmental stressors can alter offspring phenotype and increase fitness. Here, we investigate the relative and combined effects of maternal and developmental exposure to mild hypoxia (65% and 74% air saturation respectively) on the growth and development of embryos of the marine gastropod Littorina littorea. Differences in embryo morphological traits were driven by the developmental environment, whereas the maternal environment and interactive effects of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 87 publications
0
4
0
Order By: Relevance
“…In several shark species where multiple paternity is present, fertilisation is thought to occur over an extended period of time (Schmidt et al, 2010; Marino et al, 2015). In this scenario there may be discrepancies in the maternal provisioning that different embryos receive at a given embryogenic stage, as in matrotrophic species the nutrients provided to embryos by the mother depends to some extent on the trophic characteristics of the environmental conditions to which the mother is exposed (Olin et al, 2011; McCoy et al, 2020). The degree of body size variation in our results (Table 2) combined with the ∼10 month gestation period and seasonal migratory behaviour of M. henlei (Pérez-Jiménez and Sosa-Nishizaki, 2008) leads us to suggest that multiple paternity in this taxon likely does result in different embryos within a litter receiving different nutritional profiles from the mother at given embryogenic stages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In several shark species where multiple paternity is present, fertilisation is thought to occur over an extended period of time (Schmidt et al, 2010; Marino et al, 2015). In this scenario there may be discrepancies in the maternal provisioning that different embryos receive at a given embryogenic stage, as in matrotrophic species the nutrients provided to embryos by the mother depends to some extent on the trophic characteristics of the environmental conditions to which the mother is exposed (Olin et al, 2011; McCoy et al, 2020). The degree of body size variation in our results (Table 2) combined with the ∼10 month gestation period and seasonal migratory behaviour of M. henlei (Pérez-Jiménez and Sosa-Nishizaki, 2008) leads us to suggest that multiple paternity in this taxon likely does result in different embryos within a litter receiving different nutritional profiles from the mother at given embryogenic stages.…”
Section: Discussionmentioning
confidence: 99%
“…It is also important to consider that embryo morphology may also be influenced by prepartum environmental conditions (Kaplan and Phillips, 2006; Rodda and Seymour, 2008). Selective pressures associated with prepartum conditions could include sibling relatedness (Pfennig and Collins, 1993), constraints relating to the anatomy of the mother (Qualls et al, 1995), and even temporal variation in the environmental conditions experienced by the mother (Sale et al, 2007; McCoy et al, 2020). Each of these factors is yet to be considered from the perspective of elasmobranch taxa, representing a significant gap in our understanding of morphological evolution within this clade.…”
Section: Introductionmentioning
confidence: 99%
“…This value can now be used for comparisons with other L. littorea populations from different areas to investigate adaptations across the vast geographical areas this species occurs. Mccoy et al (2020) investigated L. littorea egg development under hypoxia but reported that the control group (normoxia at 14°C) reached 50% hatch after 8.8 days. Using the t 0 established it his study, this would relate to 65 DD eff , thus reasonably matching the average calculated for the current experiment (60.7 DD eff ).…”
Section: Discussionmentioning
confidence: 99%
“…Environmental hypoxia events caused by global warming and coastal eutrophication are becoming one of the most important changes in the open ocean and coastal waters worldwide. , These events can have important impacts on the abundance, survival, behavior, growth, development, and reproduction of marine organisms. The effects of hypoxia on organisms vary by species, hypoxia severity, and duration of hypoxia as well as developmental stages of organisms. The long-term consequences of hypoxia exposure of marine organisms at their early developmental stages, including adverse physiological performance, a reduced growth rate, and changed hypoxia tolerance, have been also well demonstrated in fish, mollusk, and other invertebrates . It is noted that the long-term effects of severe (<2 or <0.5 mg/L) and moderate (3–4 mg/L) hypoxia exposure on the hypoxia tolerance of marine organisms may be opposite and species-specific: for example, the zebrafish (Danio rerio) embryos that survive a severe hypoxia exposure (5% dissolved oxygen) or total anoxia (less than 0.5% dissolved oxygen) exhibited an increased hypoxia tolerance as larvae; however, the European sea bass (Dicentrarchus labrax) larvae that experienced a moderate hypoxia exposure (40% air saturation) exhibited lower resistance to hypoxia .…”
Section: Introductionmentioning
confidence: 99%